Microcirculatory vasomotor changes are associated with severity of peripheral neuropathy in patients with type 2 diabetes. (May 2013) - Sun, Pi-Chang; Kuo, Cheng-Deng; Chi, Lin-Yang; Lin, Hong-Da; Wei, Shun-Hwa; Chen, Chen-Sheng
Systemic microvascular complications are related to the presence of diabetic neuropathy. This study investigated the associations of blood flow oscillations with peripheral neuropathy in 25 controls and 3 diabetic groups including clinical (24), subclinical (27) and without neuropathy (26). Laser Doppler skin perfusion was transformed into three low-frequency subintervals corresponding to endothelial, neurogenic and myogenic vasomotor controls. The average vasomotion was significantly reduced in clinical neuropathy group and characterized by endothelial and neural but not smooth muscle–related changes. The normalized spectrums revealed a relative increase of myogenic and decrease of neurogenic activity in subclinical neuropathy group. The myogenic component showed a statistically inverse correlation with postural fall in systolic blood pressure (r = −0.32, p < 0.01). The diabetic patients with decreased low-frequency vasomotor responses were associated with increased odds ratio of peripheral neuropathy [odds ratio = 3.51 (95% confidence interval = 1.19–10.31), p = 0.02]. This study elucidated possible interaction between impaired microvascular flow motion and diabetic peripheral neuropathy. The vasomotor changes of skin microcirculation could be detected even in the absence of overt cardiovascular dysfunction.